Kewenangan Kurator Dalam Pengurusan Dan Pemberesan Harta Pailit Dalam Hal Negara Sebagai Kreditor Preferen - Venia Utami Keliat; Sunarmi Sunarmi; Bismar Nasution; T. Devi Keizerina Azwar (Mahesa Research Center, 2021)
In handling and settling of bankruptcy debtor wealth is carried out by the curator under the supervision of a judge with the main objective of using the sale of these assets to pay all debts of the bankrupt debtor proportionally (prorate parta) and based on the structure. The existence of a state towards a bankrupt company in collecting tax which is a state right. With the Constitutional Court Verdict No. 67 / PUU-XI / 2013 results in uncertainty. Which should be paid first, tax debt or labor wages. Therefore a problem arises namely what is the responsibility of the curator in handling and settlement of bankrupt assets, how Law Number 37 of 2004 Concerning Bankruptcy and Delaying Obligations of Debt Payment in protecting the duties of the curator in terms of handling and settlement bankrupt assets, how is the State's position as the preferred creditor after the Constitutional Court's verdict No. 67 / PUU-XI / 2013. The type of writing method applied in this research is normative legal research. The method of approach used is the method of legislation approach using primary, secondary and tertiary legal materials. The data needed is collected by means of library research and field research by conducting interviews and then analyzed by qualitative deductive analysis methods to produce descriptive data. Based on the results of the study it can be concluded that the. The curator cannot be punished if he has carried out his duties according to the Judge's provisions. The dispute over the right to precede only arises when there are bills for labor wages and tax debts all at once.